Higher dietary vitamin D intake is associated with better survival among older women: Results from the French EPIDOS cohort - Gautier, Jennifer; Riou, Jérémie; Schott, Anne-Marie; Blain, Hubert; Rolland, Yves; Saulnier, Patrick; Annweiler, Cédric (Frontiers in Nutrition, 2022)
Background: Hypovitaminosis D, a condition highly common among older adults, is associated with 35-percent increased all-cause mortality. In contrast, vitamin D supplementation prevents all-cause mortality. The possible role of the dietary intake of vitamin D on mortality remains yet unknown. Objectives: The objective of this prospective study was to determine all-cause mortality risk according to baseline dietary vitamin D intake among older adults while accounting for potential confounders including dietary calcium intake. Methods: Vitamin D and calcium dietary intakes were estimated at baseline from a self-administered food frequency questionnaire among 3,066 community-dwelling older women aged ≥75years, recruited in the French EPIDOS cohort between 1992-1994, and for whom information about vital status was available in 2010. Dietary vitamin D and calcium intakes were defined as low if <400IU/day or <1200mg/day, respectively. Results: The mean ± SD age of the whole cohort was 80.1± 3.6years at baseline. The median survival time from baseline for participants with low dietary vitamin D intake was 11.5years (95% confidence interval [CI]: 11.0-11.9) versus 12.2years (95% CI: 11.7-12.9) for those consuming more than 400 IU/day (p = 0.003). Among those with calcium dietary intake <1200mg/day, a vitamin D consumption of 400IU/day and over had a significant positive effect on all-cause mortality (RR: 0.86, p <0.05). However, no association was retrieved between dietary vitamin D intake and all-cause mortality among participants with dietary calcium intake ≥1200mg/day. Conclusion: Higher dietary vitamin D intake was associated with better survival in the studied cohort, specifically among those consuming less than 1200 mg/day of dietary calcium.